A genotypic analysis of five P. aeruginosa strains after biofilm infection by phages targeting different cell surface receptors - Pires, Diana P. (2017)
The Supplementary Material for this article can be found online at: http://journal.frontiersin.org/article/10.3389/fmicb. 2017.01229/full#supplementary-material